2004
DOI: 10.1016/j.neuron.2004.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Ca2+ Channels Compete for Channel Type-Preferring Slots in Altered Neurotransmission Arising from Ca2+ Channelopathy

Abstract: Several human channelopathies result from mutations in alpha1A, the pore-forming subunit of P/Q-type Ca2+ channels, conduits of presynaptic Ca2+ entry for evoked neurotransmission. We found that wild-type human alpha1A subunits supported transmission between cultured mouse hippocampal neurons equally well as endogenous mouse alpha1A, whereas introduction of impermeant human alpha1A hampered the effect of endogenous subunits. Thus, presynaptic P/Q-type channels may compete for channel type-preferring "slots" th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
145
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 61 publications
14
145
1
Order By: Relevance
“…47 In contrast, synaptic transmission was unaltered and the contribution of P/Q Ca 2ϩ channels in controlling release was decreased at synapses between hippocampal neurons transfected with human R192Q Ca V 2.1␣1 subunits. 37 The functional studies just described lead to the important conclusion that FHM1 mutations produce gainof-function of human neuronal Ca V 2.1 channels. Mutant human Ca V 2.1 channels open at lower voltages and more readily than WT channels, and Ca 2ϩ influx through mutant channels can occur in response to small depolarizations insufficient to open WT channels.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 98%
See 3 more Smart Citations
“…47 In contrast, synaptic transmission was unaltered and the contribution of P/Q Ca 2ϩ channels in controlling release was decreased at synapses between hippocampal neurons transfected with human R192Q Ca V 2.1␣1 subunits. 37 The functional studies just described lead to the important conclusion that FHM1 mutations produce gainof-function of human neuronal Ca V 2.1 channels. Mutant human Ca V 2.1 channels open at lower voltages and more readily than WT channels, and Ca 2ϩ influx through mutant channels can occur in response to small depolarizations insufficient to open WT channels.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 98%
“…In humans, mutations in the CACNA1A gene cause, in addition to FHM1, a few autosomal dominant neurological disorders characterized by cerebellar dysfunction, such as episodic ataxia type 2 (that may be associated with absence epilepsy in a few cases) and spinocerebellar ataxia type 6 9,26,27 (compare, Strupp 28 and Gomez 29 31,35,37,38 Recently, the generation of knockin mice carrying two different FHM1 mutations (R192Q and S218L) allowed the first analysis of mutant channels expressed at their endogenous level in neurons. [39][40][41] The studies in heterologous expression systems showed that the FHM1 mutations alter many biophysical properties of human Ca V 2.1 channels, in a complex way.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Biophysical analysis of FHM1 Ca 2+ channel dysfunction in heterologus systems show that the FHM1 mutations alter many biophysical properties of human Cav2.1 channels in a complex way, which is rather debateable since both loss-of-function and gain-of-function phenotypes have been reported (Cao et al 2004, Barrett et al 2005, Tottene et al 2002, Kraus et al 2000, Hans et al 1999. The most consistent effect revealed by the analysis of single-channel properties of human Ca V 2.1 channels carrying FHM1 mutations was an increase in channel open probability and in single channel Ca 2+ influx over a broad voltage range, mainly due to a shift of channel activation to more negative voltages (Tottene et al 2002, Hans et al 1999).…”
Section: C3 Functional Consequences Of Fhm1 Gene Mutations: Studiesmentioning
confidence: 99%